Performance of micromachined quartz gravimetric sensors upon electrochemical adsorption of monolayers - Kao, P.; Patwardhan, A.; Allara, D.; Tadigadapa, S.; Strutwolf, J.; Arrigan, Damien (2008)
This paper presents the results of electrochemical calibration experiments performed on micromachined quartz gravimetric sensors. The absolute mass sensitivity of bulk acoustic quartz crystal microbalance (QCM) can be improved into the sub-10-12 g range upon miniaturization of the resonator thickness and area. Using plasma etching, we have fabricated miniaturized QCMs with thicknesses of ~29 µ^m and diameters of 500 µ^m with f0=58 MHz. Resonators with 60 nm thick Ti/Pt top electrodes were used to study the electrochemically induced oxide layer formation on the metal surface, the adsorption of hydrogen, and underpotential deposition (UPD) of Cu on Pt electrodes. The performance of microQCM is compared with the performance of a frequency matched overtone mode of a commercial 5 MHz resonator. Micromachined QCMs showed expected sensitivity improvement to UPD of Cu, however an unexpected hundred fold enhancement to oxygen and ~28 times enhancement in the sensitivity to hydrogen adsorption was observed which may be due to the roughness/porosity of the electrodes. © 2008 IEEE.